2008
DOI: 10.1242/jeb.015610
|View full text |Cite
|
Sign up to set email alerts
|

The alkaline tide and ammonia excretion after voluntary feeding in freshwater rainbow trout

Abstract: SUMMARYWe investigated the potential acid-base and nitrogenous waste excretion challenges created by voluntary feeding in freshwater rainbow trout, with particular focus on the possible occurrence of an alkaline tide (a metabolic alkalosis created by gastric HCl secretion during digestion). Plasma metabolites (glucose, urea and ammonia) were measured at various time points before and after voluntary feeding to satiation (approximately 5% body mass meal of dry commercial pellets), as was the net flux of ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
72
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 84 publications
11
72
2
Order By: Relevance
“…Under these circumstances, ammonia liberated from post-prandial catabolic processes would begin to accumulate in the plasma and eventually translate into elevated rates of ammonia excretion, as was the case in the present study. This pattern is also observed in other ammoniotelic teleosts following feeding (Kaushik and Teles, 1985;Kaushik and Gomes, 1988;Alsop and Wood, 1997;Wicks and Randall, 2002;Bucking and Wood, 2008;Bucking et al, 2009;Zimmer et al, 2010). In addition, this explanation also clarifies why the increases in plasma ammonia levels (Fig.1B) and ammonia excretion rates (Fig.1A) observed in crowded and unconfined fish during the post-prandial period were of similar magnitude.…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 76%
See 2 more Smart Citations
“…Under these circumstances, ammonia liberated from post-prandial catabolic processes would begin to accumulate in the plasma and eventually translate into elevated rates of ammonia excretion, as was the case in the present study. This pattern is also observed in other ammoniotelic teleosts following feeding (Kaushik and Teles, 1985;Kaushik and Gomes, 1988;Alsop and Wood, 1997;Wicks and Randall, 2002;Bucking and Wood, 2008;Bucking et al, 2009;Zimmer et al, 2010). In addition, this explanation also clarifies why the increases in plasma ammonia levels (Fig.1B) and ammonia excretion rates (Fig.1A) observed in crowded and unconfined fish during the post-prandial period were of similar magnitude.…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 76%
“…Higher hepatic Rh mRNA expression was accompanied by an upregulation of both Rhcg1 and Rhcg2 at the gill (Fig.5A). This scenario is similar to that of most teleosts that simply excrete the majority of excess ammonia across the gills (Kaushik and Teles, 1985;Wicks and Randall, 2002;Bucking and Wood, 2008;Bucking et al, 2009). Indeed, physiological data from the present study confirmed that unconfined toadfish excreted the majority of their wastes as ammonia (Table2), and also had higher rates of ammonia excretion than their crowded counterparts.…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 67%
See 1 more Smart Citation
“…acid-base regulation (Bucking et al, 2009;Taylor et al, 2007;Taylor and Grosell, 2006;Taylor and Grosell, 2009;Wood et al, 2010), salt balance (Bucking et al, 2011;Taylor et al, 2007;Taylor and Grosell, 2006)] and freshwater [e.g. acid-base regulation (Bucking and Wood, 2008;Cooper and Wilson, 2008;Taylor et al, 2007;Wood et al, 2010), salt balance (Bucking and Wood, 2006a;Bucking and Wood, 2007;Taylor et al, 2007), water balance (Bucking and Wood, 2006b)]. In general, feeding appears to result in salinity-dependent alterations in ion, water and acid-base transport processes in order to alleviate digestion-induced disruptions in homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Wicks and Randall, 2002;Bucking and Wood, 2008), exhaustive exercise (e.g. Wood, 1988;Wang et al, 1994) or exposure to high environmental ammonia (HEA) (Wilson and Taylor, 1992;Knoph, 1996;Nawata et al, 2007), suggesting the possible function of ammonia to induce hyperventilation in these circumstances.…”
Section: Introductionmentioning
confidence: 99%